A distress-continuum, disorder-threshold model of depression: a mixed-methods, latent class analysis study of slum-dwelling young men in Bangladesh - Wahid, Syed Shabab; Sandberg, John; Sarker, Malabika; Arafat, A. S. M. Easir; Apu, Arifur Rahman; Rabbani, Atonu; Colón-Ramos, Uriyoán; Kohrt, Brandon A. (BMC psychiatry, 2021)
Binary categorical approaches to diagnosing depression have been widely criticized due to clinical limitations and potential negative consequences. In place of such categorical models of depression, a ‘staged model’ has recently been proposed to classify populations into four tiers according to severity of symptoms: ‘Wellness;’ ‘Distress;’ ‘Disorder;’ and ‘Refractory.’ However, empirical approaches to deriving this model are limited, especially with populations in low- and middle-income countries.